Note on edge irregular reflexive labelings of graphs. Issue 2 (1st August 2019) - Bača, Martin; Irfan, Muhammad; Ryan, Joe; Semaničová-Feňovčíková, Andrea; Tanna, Dushyant
Abstract: For a graph, an edge labeling and a vertex labeling are called total -labeling, where . The total -labeling is called an edge irregular reflexive -labeling of the graph, if for every two different edges and of, one has The minimum for which the graph has an edge irregular reflexive -labeling is called the reflexive edge strength of . In this paper we determine the exact value of the reflexive edge strength for cycles, Cartesian product of two cycles and for join graphs of the path and cycle with .